Current and future therapeutic approaches for the treatment of small cell lung cancer. Issue 5 (4th May 2018) - Rossi, Antonio; Tay, Rebecca; Chiramel, Jaseela; Prelaj, Arsela; Califano, Raffaele
ABSTRACT: Introduction : Small-cell lung cancer (SCLC) is a very aggressive disease characterized by a high response rate to first-line chemotherapy, but most patients relapse within 1 year with disappointing results to second-line treatments. Chemotherapy has reached a plateau of effectiveness and new therapeutic strategies are needed to change the natural history of SCLC. Areas covered : This review will focus on the current results and the future development of the therapeutic approaches for the treatment of SCLC. Expert commentary : Immunotherapy is becoming a new frontier for the management of SCLC with preliminary interesting results. To date, no targeted drugs have been approved for clinical practice but several novel agents are in an advanced stage of clinical development in SCLC.